Assessment of the Efficiency of Energy and Resource-Saving Technologies in Open Innovation and Production Systems - Jalal, Ahmed Q.; Allalaq, Hussein A. Essa; Shinkevich, Alexey I.; Kudryavtseva, Svetlana S.; Ershova, Irina G. (International Journal of Energy Economics and Policy, 2019)
The relevance of this work is determined by the fact that the issues of energy- and resource-saving technologies implementation in open production and economic systems have not been fully addressed yet and require further study and systematization of the determining factors, which is especially important on the back of the transition to a new technological pattern and the use of the emerging technological opportunity windows. The solution of the problems mentioned will reveal new opportunities for qualitative and quantitative growth of production systems by improving the innovation targeting in the field of resource saving and energy efficiency. The purpose of the article is to identify the functional dependence between the industrial production index and the indicators describing the energy- and resource-saving system in the industrial complex in order to improve the efficiency of energy- and resource-saving technologies in open innovation and production systems. The main research methods underlying the article include the method of description used to identify trends in the use of energy- and resource-saving technologies across the globe, the correlation analysis method used to identify the strength of the relationship between the industrial production index and indicators of the energy- and resource-saving system in production, and the regression analysis method used to build a regression model of the dependence between the resource-saving system and production indicators. The article touches upon the aspects of improving the energy- and resource-saving system efficiency in the framework of the innovation model in the field of production. The multidirectional nature of trends in the industrial production and the use of energy- and resource-saving technologies in the industry of developing countries is revealed; the functional relationship between the use of waste in industrial enterprises and shipped industrial products on the example of developing countries is proved. The materials of the article can be used in the development of strategies and programs aimed to improve the energy- and resource-saving system efficiency in petrochemical companies of developing countries, taking into account the emerging technological opportunity windows and technology readiness of the production for innovative transformations. Keywords: energy saving, resource saving, open innovations, energy efficiency JEL Classifications: Ðž32, L60, L23, D24 DOI: https://doi.org/10.32479/ijeep.8253